Pelatihan Pembuatan Teh Herbal Berbasis Bunga Telang (Clitoria ternatea L.) Dan Pemasaran Digital Untuk Mewujudkan Kemandirian Ekonomi Remaja Di Kelurahan Manggala - Hasriwiani Habo Abbas; Nuruh Husnah; A.Rizki Amelia Ap; Ilmi Kumaera; Alifah Fauziah; Ayunda (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
In the era of rapid digital advancement, new challenges have emerged related to adolescent behavior. High levels of internet use—exceeding five hours per day according to the 2022 APJII survey—indicate a pattern of gadget usage that is largely unproductive. This condition is closely linked to an increasingly sedentary lifestyle and a decline in youth participation in entrepreneurial activities, community engagement, and personal development. In addition, the abundance of butterfly pea flowers (Clitoria ternatea L.) growing around residential areas in Kelurahan Manggala has not been fully utilized; most plants serve only as decorative ornamentals without further economic value. Therefore, this community service program aimed to empower adolescents by training them to produce butterfly pea herbal tea as a means to strengthen their economic independence. The program employed lectures, hands-on practice, group discussions, and demonstrations. It was conducted on 18 October 2025 at the Pokja KB Office Hall in Kelurahan Manggala. The training on herbal tea production resulted in notable improvements, with participants’ knowledge increasing to 90% and skill levels rising to 80%. The training materials emphasized selecting high-quality flowers, proper drying techniques, and basic sanitation standards. Digital marketing training also showed significant gains, with knowledge improving to 90% and skills to 85%. This session focused on the use of social media platforms, branding strategies, and safe digital transaction practices. Overall, the program effectively enhanced adolescents’ competencies in producing butterfly pea herbal tea and applying digital marketing, thereby creating opportunities for the development of micro-enterprise initiatives based on local botanical resources.